1996
DOI: 10.2337/diacare.19.12.1344
|View full text |Cite
|
Sign up to set email alerts
|

A Twofold Excess Mortality Among Black Compared With White IDDM Patients in Allegheny County, Pennsylvania

Abstract: The data suggest that some of the excess mortality in black IDDM patients may be preventable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 9 publications
3
16
0
Order By: Relevance
“…Greater contact with a diabetes specialist care team has also been suggested to be related to a reduced risk of death in Pittsburgh (18). Another component of the higher mortality in the U.S. is the higher mortality of African-Americans, which has previously been reported as a twofold excess mortality in the same cohort (19). The difference in prognosis after 20 years duration of diabetes was evident.…”
Section: Discussionmentioning
confidence: 73%
“…Greater contact with a diabetes specialist care team has also been suggested to be related to a reduced risk of death in Pittsburgh (18). Another component of the higher mortality in the U.S. is the higher mortality of African-Americans, which has previously been reported as a twofold excess mortality in the same cohort (19). The difference in prognosis after 20 years duration of diabetes was evident.…”
Section: Discussionmentioning
confidence: 73%
“…In other autoimmune diseases, such as systemic lupus erythematosus and type 1 diabetes mellitus, significant differences have been identified both in the clinical features and severity of disease between African Americans and whites. [9][10][11][12][13][14][15][16] Analogous data exist for rheumatoid arthritis in which differences in the manifestations of the disease in patients of African American, North Indian, or Pakistani origin compared with whites have been reported. 17 18 To investigate whether such racial differences may also apply in AIH, we have undertaken a systematic review of EC and non-EC patients referred to our outpatient clinics between 1983 and 1999 with respect to their presenting features, response to therapy, and outcome.…”
mentioning
confidence: 77%
“…This study, in a cohort of minority subjects with childhood-onset diabetes in Chicago, identified increased mortality risk among subjects with postpubertal onset. Previous studies of mortality from childhood-onset diabetes have not distinguished cases with postpubertal onset (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) or type 1 versus type 2 diabetes or have only studied patients presumed to have type 1 diabetes (3,5,6,8,10,14). Authors of one study comparing international death rates asserted that the bulk of the excess mortality should be attributed to type 1 diabetes (9).…”
Section: Methodsmentioning
confidence: 99%
“…Mortality for youth-onset diabetes in Allegheny County, Pennsylvania (9), was found to be 2.5 times higher than in Israel and 1.6 times higher than in Finland, suggesting that some proportion could be preventable. In Allegheny County (13), African Americans died more often from acute complications of diabetes than did whites; Roy et al (14) also found increased mortality among African-American patients with type 1 diabetes in New Jersey. DiLiberti et al (15) used national data to study temporal trends for childhood diabetes mortality.…”
mentioning
confidence: 99%